Microsurgery in complex trauma of pelvic limb in a pediatric patient: case report - Banegas-Ruíz, Rodrigo; Loyo Soriano, Luis E.; Gómez-Mendoza, Francisco Fabián; Mendoza-Aceves, Rodrigo A.; Hernández, Rigoberto Román; Méndez, Christian Porras; Valderrama-Treviño, Alan I.; Ortega, Emilio Pérez; Alba, Ismael Vejar; Ulloa, Rubén Olivares; Hernández-Arteaga, Leonel Dalain; Járez-Duarte, Erick Salvador; et al. (International Journal of Research in Medical Sciences, 2019)
Complex trauma is defined as the condition secondary to the exchange of kinetic energy of two or more tissues in one limb. This entity is a surgical emergency that can have many sequelae and can even result in limb loss. An 11-year-old female patient presents complex pelvic limb trauma secondary to contuse injury caused by a helicopter’s rotor blades. Pelvic limb reconstruction was performed with iliac crest bone graft, the fracture was stabilized with an external fixator and the skin defect was covered with an anterolateral microvascular thigh flap (ALT). There was an adequate integration of the bone graft with adequate skin coverage thanks to the ALT thigh flap. The patient presented discreet limb shortening as consequence. Currently, microsurgery is the only medical option that meets the objectives of limb reconstruction. Microsurgical techniques can be used in pediatric and adult patients. The success of any recovery from complex trauma is vigorous surgical cleaning, avoiding sequential and/or multiple washes.